High penetrance and similar disease progression in probands and in family members with arrhythmogenic cardiomyopathy. (1st September 2019) - Chivulescu, Monica; Lie, Øyvind H; Popescu, Bogdan A; Skulstad, Helge; Edvardsen, Thor; Jurcut, Ruxandra O; Haugaa, Kristina H
Abstract: Aims: We aimed to assess structural progression in arrhythmogenic cardiomyopathy (AC) patients and mutation-positive family members and its impact on arrhythmic outcome in a longitudinal cohort study. Methods and results: Structural progression was defined as the development of new Task Force imaging criteria from inclusion to follow-up and progression rates as annual changes in imaging parameters. We included 144 AC patients and family members (48% female, 47% probands, 40 ± 16 years old). At genetic diagnosis and inclusion, 58% of family members had penetrant AC disease. During 7.0 [inter-quartile range (IQR) 4.5–9.4] years of follow-up, 47% of family members without AC at inclusion developed AC criteria, resulting in a yearly new AC penetrance of 8%. Probands and family members had a similar progression rate of right ventricular outflow tract diameter (0.5 mm/year vs. 0.6 mm/year, P  = 0.28) by mixed model analysis of 598 echocardiographic examinations. Right ventricular fractional area change progression rate was even higher in family members (−0.6%/year vs. −0.8%/year, P  < 0.01). Among 86 patients without overt structural disease or arrhythmic history at inclusion, a first severe ventricular arrhythmic event occurred in 8 (9%), of which 7 (88%) had concomitant structural progression. Structural progression was associated with higher incidence of severe ventricular arrhythmic events adjusted for age, sex, and proband status (HR 21.24, 95% CI 2.47–182.81, P  < 0.01). Conclusion: More than half of family members had AC criteria at genetic diagnosis and yearly AC penetrance was 8%. Structural progression was similar in probands and family members and was associated with higher incidence of severe ventricular arrhythmic events.